The influence of commitment on employees’ sense of belongingness, and the consequences on employees’ turnover intentions in high-commitment organizations: A study at the Royal Netherlands Navy. - Waardenburg, Lauren (Student Undergraduate Research E-journal!, 2016)
This study has been conducted in order to further understand the experience of belongingness of employees and to identify how organizations can reduce the turnover intentions of their employees by using the experience of belongingness, complemented by the effect of commitment (formal and informal). Two forms of belongingness were developed: (1) personal belongingness and (2) organizational belongingness. The results of this study indicate that a positive experience of organizational belongingness reduces the turnover intentions of those employees. Complementing this with formal commitment could increase the positive experience. Personal belongingness could either reduce or increase the intention to leave; informal commitment could be used to reduce this intention.